A Load Balancing Based Cloud Computing Techniques and Challenges (International Journal of Scientific Research and Management (IJSRM), 2014)
Cloud Computing refers to the use and access of multiple server based computational resources via a digital network(WAN).Cloud users may access the resources using computer note book, pad computer, smart phone, or other device. In cloud computing applications are provided and managed by the cloud server and data is also stored remotely in cloud configuration. As Cloud Computing is growing rapidly and clients are demanding more services and better results, load balancing for the Cloud has become a very interesting and important research area. Load balancing ensures that all the processor in the system or every node in the network does approximately the equal amount of work at any instant of time. Here in this paper we have discussed many different load balancing techniques used to solve the issue in cloud computing environment. This paper presents various approaches given by the researchers using the load balancing techniques.